Pemberian Sanksi Tindak Pidana Penyebaran Berita Bohong Yang Mengakibatkan Keonaran Publik Dalam Sistem Hukum Di Indonesia - Lubis, Muhammad Ridwan (Universitas Medan Area, 2023)
Inaccurate and factually incorrect reporting can lead to the dissemination of false information, resulting in public disorder. This occurrence raises concerns about the need for stringent criminal sanctions against perpetrators of spreading false news, especially in the context of online media. The term